2021
DOI: 10.1111/os.12878
|View full text |Cite
|
Sign up to set email alerts
|

H3.3 K36M Mutation as a Clinical Diagnosis Method of Suspected Chondroblastoma Cases

Abstract: Objective Whether H3.3 K36M mutation (H3K36M) could be an approach if the diagnosis of chondroblastoma (CB) patients was indistinct and it was suspected to be unclear clinically. Methods We reviewed and compared our clinical experiences of CB cases and some suspected cases, which were not diagnosed distinctly, between 2013 to 2019. A total of 15 male and four female cases included in this study were seperated into two groups, CB group and suspected case (SC) group. The CB group included 13 men and 3 women, wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 15 publications
1
1
0
Order By: Relevance
“…4 The monoclonal H3.3K36M antibody directed against K36M mutation is an useful ancillary diagnostic tool for the diagnosis of chondroblastoma. 8,17 Similar to the present study Rekhamper et al also found positive nuclear staining in all the cases of chondroblastoma tested. The authors further performed DOG1 IHC and found positivity in 11 out of 14 cases.…”
Section: Discussionsupporting
confidence: 90%
“…4 The monoclonal H3.3K36M antibody directed against K36M mutation is an useful ancillary diagnostic tool for the diagnosis of chondroblastoma. 8,17 Similar to the present study Rekhamper et al also found positive nuclear staining in all the cases of chondroblastoma tested. The authors further performed DOG1 IHC and found positivity in 11 out of 14 cases.…”
Section: Discussionsupporting
confidence: 90%
“…Histologically, there is an increase in chondroblasts, the immature precursors to chondrocytes, and giant cells [3] . Chondroblastomas were found to express an H3F3B K36M point mutation which can aid in the correct identification of the tumor [8] . Intralesional curettage with adjuvants, such as phenol or hydrogen peroxide, is the gold standard for treatment [1] .…”
Section: Introductionmentioning
confidence: 99%